ANTIBACTERIAL ACTIVITY OF ALLIUM SATIVUM (GARLIC) AND IDENTIFICATION OF ACTIVE COMPOUND BY GC-MS ANALYSIS - KARWAN SEDEEQ MOHAMMED (International Journal of Pharma and Bio Sciences, 2013)
In this study, different solvent extracts of garlic such as Ethanol, Methanol, Butanol, Acetone and Hexane was used for screening of antibacterial activity. The extracts were tested against both gram positive and gram negative bacteria such as B. subtilis, S. aureus, P.auregunisa, and S. typhi. The antibacterial activity was determined by agar well diffusion method on Mueller-Hinton Agar plates. Also, the inhibitory activity was tested against fungal species A. niger. All extracts showed inhibitory action against all four bacteria as well as fungi. The bioactive compound was identified by GC-MS analysis as 2-Furancarboxaldehyde, 5-(hydroxymethyl). These findings claim capacity and future use of this compound for drug development. The future work will be to determine toxicity, side effects and pharmaco-kinetic properties of this compound.